2014
DOI: 10.1074/jbc.m114.602961
|View full text |Cite
|
Sign up to set email alerts
|

Different Interaction Modes for Protein-disulfide Isomerase (PDI) as an Efficient Regulator and a Specific Substrate of Endoplasmic Reticulum Oxidoreductin-1α (Ero1α)

Abstract: Background: Ero1␣ and PDI constitute the pivotal oxidative protein folding pathway in mammalian ER. Results: Both catalytic domains of PDI and PDI homologues rapidly regulate Ero1␣ activity while Ero1␣ asymmetrically oxidizes PDI. Conclusion:The modes for PDI as efficient regulator and specific substrate of Ero1␣ are different. Significance: This study reveals how Ero1␣-PDI interplay ensures oxidative protein folding homeostatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 41 publications
3
55
1
Order By: Relevance
“…In the human system, Ero1␣ binds to the bЈ domain of PDI via a strong hydrophobic interaction (12,17,18), which results in the preferential oxidation of the aЈ domain rather than the a domain of PDI (12,19,20). In contrast, the binding interaction between Ero1p and Pdi1p is weak (18), and Ero1p oxidizes domain a of Pdi1p faster than domain aЈ (21).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In the human system, Ero1␣ binds to the bЈ domain of PDI via a strong hydrophobic interaction (12,17,18), which results in the preferential oxidation of the aЈ domain rather than the a domain of PDI (12,19,20). In contrast, the binding interaction between Ero1p and Pdi1p is weak (18), and Ero1p oxidizes domain a of Pdi1p faster than domain aЈ (21).…”
mentioning
confidence: 99%
“…PDI predominantly in its reduced state can reduce the regulatory disulfides of Ero1 to generate more activated Ero1, and once sufficient PDI is oxidized by Ero1, it can re-oxidize the regulatory disulfides of Ero1 to inhibit its activity (18, 24 -26). It has been found that human PDI reduces and also re-oxidizes the regulatory disulfides of Ero1␣ very fast (18), whereas yeast Pdi1p is more potent to inhibit Ero1p than to activate Ero1p (25). Coincidently, in cells endogenous Ero1␣ exists in mixed states of oxidized and semioxidized (24,27), whereas Ero1p is almost fully oxidized (25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2). 38 Structural and functional studies have been conducted mainly on mammalian Ero1, where there are 2 isoforms known (a, b). 39 Ero1-a is widely expressed, yet both isoforms have enzymatic activities that are controlled by regulatory disulfides formed among catalytic and non-catalytic cysteines to avoid futile oxidation cycles, which prevents excess hydrogen peroxide production.…”
Section: Protein Disulfide Isomerases -Pdi'smentioning
confidence: 99%